Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 3 - Differentiation - 3.5 Higher Derivatives - Exercises - Page 135: 19



Work Step by Step

Since $ y=4t^{-3}+3t^2$, then $$\frac{d y}{d t}=-12 t^{-4}+6t, \quad \frac{d^2 y}{d t^2}=48 t^{-5}+6.$$ Hence, $ \left.\frac{d^{2} y}{d t^{2}}\right|_{t=1}=48+6=54 $.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.